Understanding the intention-behavior gap: The role of intention strength - Conner, Mark; Norman, Paul (Frontiers in Psychology, 2022)
This paper overviews recent research on the intention-behavior gap, focusing on moderators of the intention-behavior relationship. The paper draws on the concept of intention strength to make two important points. First, strong intentions provide better predictions of behavior, thereby reducing the intention-behavior gap. However, strong intentions have the additional features of being more stable over time, less pliable in the face of interventions to change them, and more likely to bias information processing about engaging in the behavior. These four features of intention strength are not independent. For example, stable intentions are likely to provide better predictions of behavior. Second, various predictors of strength (e.g., importance, certainty, extremity) may also constitute important, but little studied, moderators of the intention-behavior relationship. Moreover, the effects of these moderators of the intention-behavior relationship may be mediated through intention stability (and perhaps other features of intention strength). Future research on the intention-behavior gap would benefit from a more systematic consideration of a broad range of moderators of the intention-behavior relationship both individually and in combination. In addition, future research could usefully explore how these moderating effects might be explained. Such a systematic approach may further our understanding of the intention-behavior gap in relation to physical activity and other behaviors.